지역문화자원과 B급 문화를 활용한 캐릭터 이모티콘 개발: 도봉구 캐릭터 이모티콘 제작을 중심으로 - 남현아(Hyeon-A Nam); 김혜경(Hye-Kyung Kim) (디지털콘텐츠학회논문지, 2023)
스마트폰 보급과 더불어 메신저의 활성화, 그로 인한 이모티콘 캐릭터의 영향력이 커지면서 각 지역에서도 이모티콘을 제작하고 배포하는 홍보 방식을 택하고 있다. 이에 따라 10대, 20대에게 도봉을 홍보하고자 지역문화자원을 이용해 캐릭터 이모티콘을 제작했으며, 이때 해당 연령층에게 영향력을 많이 미치는 B급 문화 요소를 활용했다. 지자체에서는 이모티콘을 만들 때, 타겟을 명확히 하고 최신 트렌드를 반영해야 한다. 또한, 지자체 이모티콘이 가지는 확장성을 고려해야 하며, 이모티콘 캐릭터 개발 시에 탄탄한 스토리텔링과 설정이 수반되어야 한다. 본 연구에서 이모티콘 개발 과정을 제시함으로써 지자체 이모티콘이 각 지역의 인지도를 높이는 데 도움을 주는 수단으로 적절히 활용되는 데 도움을 줄 수 있으리라 기대한다. The increasing prevalence of smartphones, messaging apps, and emoticon usage has resulted in each local administration developing its own system of producing and disseminating promotional emoticons. To target teenagers and young people in the twenties, we have utilized local cultural resources to design character emoticons and integrated B-cultural elements that heavily resonate with them, as a part of our strategy to promote Dobong. When devising emoticons, local administrations should be precise about their intended targets and keep up with the current trends. Additionally, they should bear in mind the expandability of local emoticons and guarantee that the creation of emoticon characters is accompanied by effective storytelling. By detailing the process of emoticon development, in this study, we aim to assist local governments in utilizing emoticons as an appropriate means of enhancing awareness of individual regions. KCI Citation Count: 0